Satisfaction with caregivers during labour among low risk women in the Netherlands: the association with planned place of birth and transfer of care during labour - Geerts, Caroline C. (BMC Pregnancy Childbirth, 2017)
BACKGROUND: The caregiver has an important influence on women’s birth experiences. When transfer of care during labour is necessary, care is handed over from one caregiver to the other, and this might influence satisfaction with care. It is speculated that satisfaction with care is affected in particular for women who need to be transferred from home to hospital. We examined the level of satisfaction with the caregiver among women with planned home versus planned hospital birth in midwife-led care. METHODS: We used data from the prospective multicentre DELIVER (Data EersteLIjns VERloskunde) cohort-study, conducted in 2009 and 2010 in the Netherlands. Women filled in a postpartum questionnaire which contained elements of the Consumer Quality index. This instrument measures 'general rate of  satisfaction with the caregiver’ (scale from 1 to 10, with cut-off of below 9) and ‘quality of treatment by the caregiver’ (containing 7 items on a 4 point Likert scale, with cut-off of mean of 4 or lower). RESULTS: Women who planned a home birth (n = 1372) significantly more often rated 'quality of treatment by caregiver' high than women who planned a hospital birth (n = 829). Primiparous women who planned a home birth significantly more often had a high rate (9 or 10) for ‘general satisfaction with caregiver’ (adj.OR 1.48; 95% CI 1.1, 2.0). Also, primiparous women who planned a home birth and had care transferred during labour (331/553; 60%) significantly more often had a high rate (9 or 10) for ‘general satisfaction’ compared to those who planned a hospital birth and who had care transferred (1.44; 1.0–2.1). Furthermore, they significantly more often rated ‘quality of treatment by caregiver’ high, than 276/414 (67%) primiparous women who planned a hospital birth and who had care transferred (1.65; 1.2–2.3). No differences were observed for multiparous women who had planned home or hospital birth and who had care transferred. CONCLUSIONS: Planning home birth is associated to a good experience of quality of care by the caregiver. Transferred planned home birth compared to a transferred planned hospital birth does not lead to a more negative experience of care received from the caregiver. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12884-017-1410-9) contains supplementary material, which is available to authorized users.